Dampak Fotoperiode dan Suplementasi Tepung Daun Kelor pada Karakteristik Karkas dan Morfometri Organ Viscera Itik Pekin - Kasiyati, Kasiyati; Damayanti, Theresia; Djaelani, Muhammad Anwar (Jurnal Veteriner, 2022)
The external factors that are responsible for determining poultry production are light and nutrition. This study was designed to evaluating the photoperiod combined with Moringa leaf meal supplementation on carcass weight and viscera organ weight of Pekin ducks. The study used 40 Pekin ducks in a completely randomized design with a 2×4 factorial arrangement. The first factors was the photoperiod consisted of 2 levels i.e., 20L:4D and 24L:0D. The second factor was dose of Moringa leaf meal consisted of 4 levels i.e., 0; 2; 4; and 6%. Data were analyzed by two-way ANOVA. Each main factor or interaction between the main factors had no significant effect (P>0.05) on slaughter weight, carcass weight, and carcass commercial cut. Abdominal fat weight was lower by 44.70% with 4% Moringa leaf meal supplementation. Photoperiod or supplementation with Moringa leaf meal were significantly different (P<0.05) in intestinal length. We conclude that photoperiod, supplementation of Moringa leaf meal, or the combination of photoperiod with supplementation of Moringa leaf meal did not adverse affect on the carcass characteristics and viscera organs weight of Pekin ducks. Moreover, Moringa leaf meal supplementation at a concentration 4% can be applied to Pekin ducks to reduce the formation of abdominal fat thereby increasing the percentage of carcass.